Development of Mathematical Learning Model Using Activity-Based Learning - et. al., Dr,Yupadee Panarach, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were to 1) develop the mathematical learning model using activity-based learning, 2) study learning outcomes after using mathematical learning model using activity-based learning. The samples were 28 pre-service teachers in mathematics program who participated in creating and developing the model, and 29 seventh grade who learned mathematics with the mathematical learning model using activity-based learning. The research instruments were the process of action research, the mathematics achievement test, the work commitment questionnaire, and the attitude toward mathematics questionnaire. The data were analyzed by mean, standard deviation, t-test dependent (p<.05), and content analysis. The results found that: 1) the mathematical learning model using activity-based learning was a process of learning management focusing on allowing students to practice individually and in groups in order to be able to create ones’ own knowledge from the practice. Competition activities between groups were organized to encourage joyfulness which everyone had an opportunity to present knowledge. Students were also given compliments and encouragement which helped boost their self-esteem. The five steps of the mathematical learning model using activity-based learning included preparation, learning, group activities, competition, and summarization and compliment; 2) the seventh graders’ mathematics achievement after receiving the mathematical learning model using activity-based learning was higher than the criteria of 60 percent at .05 level of significance. Overall, their level of work commitment and attitudes toward mathematics were considered high. Moreover, it was found that the pre-service teachers had abilities to manage learning in terms of designing learning management, developing lesson plans, developing materials and equipment, constructing a learning behavior questionnaire for learners, and learning the role of teachers from teaching practice and observing classroom teaching